2005
DOI: 10.1080/09602010443000119
|View full text |Cite
|
Sign up to set email alerts
|

Impaired sustained attention and error awareness in traumatic brain injury: Implications for insight

Abstract: The processes of error awareness and sustained attention were investigated in 18 traumatic brain injury (TBI) individuals and 16 matched control participants. In Experiment 1, we found that: (1) in comparison to controls, TBI participants displayed reduced sustained attention and awareness of error during the Sustained Attention to Response Task; (2) degree of error awareness was strongly correlated with sustained attention capacity, even with severity of injury partialed out; and (3) that error feedback signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 30 publications
6
53
0
Order By: Relevance
“…Other studies have found similar results to Noe et al (2005) showing that certain measures of executive function and memory predict awareness (McAvinue et al, 2005;Ownsworth et al, 2002;Trudel et al, 1998). The present study only partially replicated some of these findings by showing an association between sustained attention and onlineemergent awareness and online-anticipatory awareness.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Other studies have found similar results to Noe et al (2005) showing that certain measures of executive function and memory predict awareness (McAvinue et al, 2005;Ownsworth et al, 2002;Trudel et al, 1998). The present study only partially replicated some of these findings by showing an association between sustained attention and onlineemergent awareness and online-anticipatory awareness.…”
Section: Discussionsupporting
confidence: 90%
“…The association between sustained attention, onlineemergent awareness and online-anticipatory awareness may suggest a possible route for rehabilitation, because it has been shown in a study using similar methodology to the present one that the provision of auditory feedback on error led to an improvement in sustained attention performance on the SART for TBI participants. Although it was unclear whether feedback on error enhanced error awareness or general arousal, the possibility that feedback on error may improve online error-monitoring certainly merits further investigation (McAvinue et al, 2005). Despite the small patient sample size (n 5 31) in the present study, the distinct lack of association between the composite scores of metacognitive knowledge and the two online-awareness types, strongly suggests that previous studies may not have examined the whole, multifaceted picture of awareness of deficits following TBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, from the motor perspective, self-reported task-related thoughts elicited after the SART likely reflect awareness of task performance and may even be influenced by performance itself (performance appraisal), e.g., a sportsperson following a match, stewing over a game in which they made many mistakes. McAvinue, O'Keefe, McMackin, & Robertson (2005) observed that people were aware of their SART commission errors 99.1% of the time. People are fully aware of their performance on the task.…”
mentioning
confidence: 99%